Instilling Religious Character Values in Nadran Tradition for Fisherman Communities in Banten, Indonesia - Wasehudin, Wasehudin; Rahim, Rahimin Affandi Abdul; Masitoh, Itoh; Rahman, Mohammad Taufiq; Syafe'i, Imam (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2024)
Fishermen all over the world have traditions to gather with their families and friends to give thanks for their harvest and the abundance of the sea. This study described the existence, implementation, and religious values of the Nadran tradition in the coastal areas of Pandeglang Regency of Banten, Indonesia. The research used qualitative research with the Anthropology of education as the data analysis tool, especially through cultural transmission theory. This research found that there had been a process of cultural transmission through the Nadran ceremony from one individual or group to another group. Then, in terms of context, the ceremony is still in accordance with past generations. However, in terms of content and method, there have been changes. It found that the philosophical value of the nadran tradition in the Islamic view is that culture is drawn to religion because in the Panimbang and Labuan areas, nadran events, which always used to use wayang golek (puppet shows), have now been replaced with other activities such as prayer together (istigosah), religious lectures, and other Islamic activities. It indicates the existing cultural norms inserted into Islamic religious and cultural values. Even though the buffalo head offerings are still used, this nadran expresses gratitude to God. Apart from being a tourist attraction, this nadran can also instill religious character values in the younger generation.